Attitude towards E-learning Among Students: Evidence from A Malaysian Public University - Kamarulzaman, Y.; Madun, A.; Farinda, A.G. (British Journal of Arts and Social Sciences, 2011)
The study examines students’ experience in using e-learning as a collaborative learning tool. A qualitative methodology used in this study is based on content analysis of online forums and survey among 144 undergraduate students at University of Malaya, Malaysia who have responded to online forums posted on a few course websites through Moodle. Using Rogers' (1995) diffusion of innovations model, this study attempts to understand the factors that influence the adoption of Moodle e-learning system based on users’ own experience. Although in this case the students have no choices and are required to use Moodle, the study finds that there are elements of relative advantages, compatibility and complexity for students to adopt Moodle. Furthermore, the positive experience among students using Moodle motivates them to continuously use Moodle. Overall, the results provide insights and recommendations to the government, learning institutions, lecturers and instructors to accelerate the adoption of e-learning in Malaysia.